The Past, Present and Future of COVID-19 Associated Mucormycosis: A Rapid Review. (May 2022) - Sarfraz, Zouina; Sarfraz, Azza; Jaiswal, Vikash; Poudel, Sujan; Bano, Shehar; Hanif, Muhammad; Singh Shrestha, Prakriti; Sarfraz, Muzna; Michel, George; Cherrez-Ojeda, Ivan
Coronavirus disease 2019 (COVID-19) is caused by SARS-CoV-2, which is known for the multiple mutations and forms that have rapidly spread across the world. With the imminent challenges faced by low- and middle-income countries in curbing the public health fallbacks due to limited resources, mucormycosis emerged as a fungal infection associated with high mortality. In this rapid review, we explored MEDLINE, Cochrane, Web of Science, WHO Global Database, and the search engine—Google Scholar for articles listed until July 2021 and presented a narrative synthesis of findings from 39 articles. The epidemiology, causative factors, incidence parameters, pharmacological treatment, and recommendations for low- and middle-income countries are enlisted. This study concludes that a majority of the globally reported COVID-19 associated mucormycosis cases stemmed from India. Individuals receiving systemic corticosteroids or who have a history of diabetes mellitus are more prone to contracting the disease. Public health authorities in LMIC are recommended to strengthen antifungal therapies for COVID-19 associated mucormycosis and to strategize reduction in diabetes mellitus prevalence.